THE EFFECT OF IMMERSION DURATION OF NON-DENTAL GLASS FIBER REINFORCED COMPOSITE IN ARTIFICIAL SALIVA ON TENSILE STRENGTH - Hadianto, Eko; Santoso, Lyra Arnetta; Ratnawati, Irma Dewi; Suhartono, Budi (Odonto : Dental Journal, 2024)
Background: The type of fiber often used in dentistry is E-glass fiber, which has limited availability and relatively high prices. Non-dental glass fiber can be employed as an alternative in dentistry because its composition is nearly identical to E-glass fiber. Exposure of restorative materials to artificial saliva, designed to mimic the properties of normal human saliva, affects the mechanical properties of non dental glass fiber, including tensile strength. This research aims to determine the effect of immersion duration of non-dental glass fiber reinforced composite in artificial saliva on tensile strength.Method: The research method used is laboratory experimental analytic with a post-test only control group design. Samples are divided into three treatment groups with immersion in artificial saliva for three times (2, 7, and 14 days). Tensile strength is conducted using a Universal Testing Machine (UTM).Conclusion: The conclusion drawn from this research is that immersion duration in artificial saliva has a significant effect on tensile strength of non-dental glass fiber reinforced composite. The tensile strength of non-dental glass fiber reinforced composite after immersion for 14 days shows higher results compared to immersion for 7 and 2 days.